2018
DOI: 10.1507/endocrj.ej17-0319
|View full text |Cite
|
Sign up to set email alerts
|

Warthin-like papillary thyroid carcinoma with immunoglobulin G4-positive plasma cells possibly related to Hashimoto’s thyroiditis

Abstract: Abstract. Hashimoto's thyroiditis with heavy lymphoplasmacytic infiltration is a common comorbidity of immunoglobulin G4 (IgG4)-related thyroiditis and Warthin-like papillary thyroid carcinoma (WL-PTC). We hypothesized that WL-PTC may have a strong association with IgG4-related thyroiditis. To validate this hypothesis, we clinically and immunohistochemically studied 17 WL-PTC cases. Fourteen patients (82.4%) had anti-thyroglobulin antibody and were confirmed to have Hashimoto's thyroiditis through microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…WVPTC is a rare subgroup of oncocytic variant [1] PTC, with about 162 cases reported in the English literature up to now [4,5,7,8]. Similar to previous reports, we found that WVPTC were more often seen in female patients (27/32,84.4%) with a relative high age (mean age, 51.0±10.8 years old).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…WVPTC is a rare subgroup of oncocytic variant [1] PTC, with about 162 cases reported in the English literature up to now [4,5,7,8]. Similar to previous reports, we found that WVPTC were more often seen in female patients (27/32,84.4%) with a relative high age (mean age, 51.0±10.8 years old).…”
Section: Discussionsupporting
confidence: 88%
“…After a thorough literature searching, we found that most of the articles published were about the pathological characteristics of WVPTCs [8,[17][18][19]. It is widely accepted that WVPTC is morphologically characterized by a papillary architecture with an oncocytic epithelial lining and lymphoplasmacytic core infiltrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 4 There is thus a close relationship between the pathogeneses of these two diseases. Although the exact mechanism linking these diseases is not clear, there are currently three main hypotheses: 1) HT is a precancerous lesion of PTC; 2 , 23 2) the hypothesis of chronic inflammation; and 3) HT and PTC have common causes, potentially including immune factors (both thyroid globulin antibody and microsomal antibody have been found in the blood of HT and PTC patients), 24 26 endocrine factors (HT can cause hypothyroidism and increase reactive thyrotropin, which can in turn cause carcinogenesis), 27 31 and radioactive factors (exposure to X-rays can lead to thyroid inflammation and carcinogenesis, via the same mechanism). 32 37 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incidence of HT combined with PTC has also increased significantly as the incidence of HT and PTC has increased year by year, and the correlation between the two has also become a hot spot in medical research [17]. Some scholars studied the pathological tissue sections of PTC and found that the surrounding area of PTC was often accompanied by infiltration of immune inflammatory cells such as macrophages, mast cells, and lymphocytes [18]. HT and PTC coexist frequently and both have immune inflammatory cell infiltration, which proves that there is a certain immunological relationship between them.…”
Section: Discussionmentioning
confidence: 99%